2008
DOI: 10.1590/s0102-261x2008000200009
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal characteristics of Outgoing Longwave Radiation (OLR): an update

Abstract: ABSTRACT.A study of the Outgoing longwave radiation (OLR) values (Unit, W/m 2 ) observed by various satellites during revealed that the OLR values varied considerably from one geographical region to another (∼100-300 units). The climatology was latitude dependent. At middle and high latitudes, the range (minimum to maximum) was ∼40-60 units, with maximum in local summer and minimum in local winter, but at lower latitudes, the range reduced considerably and was uncertain near equator. Near equator, the long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Among these, TSI is almost constant (often called 'Solar Constant'). Hence, the variations of terrestrial weather and climate should have a considerable contribution from the space and time variations of OLR (Kane 2008). So it is understandable that enhanced TIR emission, i.e., thermal anomaly will also be reflected in anomalous OLR.…”
Section: Yamnotri Earthquake (M W 51) Indiamentioning
confidence: 99%
“…Among these, TSI is almost constant (often called 'Solar Constant'). Hence, the variations of terrestrial weather and climate should have a considerable contribution from the space and time variations of OLR (Kane 2008). So it is understandable that enhanced TIR emission, i.e., thermal anomaly will also be reflected in anomalous OLR.…”
Section: Yamnotri Earthquake (M W 51) Indiamentioning
confidence: 99%
“…The analysis of ground surface parameters prior to earthquakes in different areas revealed that temperature rise occurred in a large area around the epicenter and its vicinity several months to a week before the onset of the earthquake (Cervone et al, 2006;Tronin et al, 2002, Tronin et al, 2004Pulinets et al, 2006;Xiong et al, 2010). Furthermore, significant anomalies in outgoing long-wave radiation were observed (Gruber et al, 1984;Ouzounov et al, 2007;Rawat et al, 2011;Kane, 2008;Zhang et al, 2017). Among the atmospheric parameters, the concentrations of CO 2 , CH 4, and other gases increased in the seismic breeding zone prior to the earthquake due to underground gas overflow within this region.…”
Section: Introductionmentioning
confidence: 99%
“…These events are ocean-atmosphere interaction phenomena associated with changes in climatological patterns of SST (Sea Surface Temperature), trade winds, surface pressure (Rasmusson and Carpenter, 1982;Kousky, 1984), and emission of longwave radiation by the ocean in the Equatorial Pacific region (Kane, 2008), thus changing the energy balance of the energy transformations that occur in the atmosphere-land-ocean system (Wallace and Hobbs, 2006). The El Niño episodes produce anomalous heat and water vapor fluxes into the tropical Pacific Ocean and the atmosphere.…”
Section: Introductionmentioning
confidence: 99%